If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t(3t + 19) = 40 Reorder the terms: t(19 + 3t) = 40 (19 * t + 3t * t) = 40 (19t + 3t2) = 40 Solving 19t + 3t2 = 40 Solving for variable 't'. Reorder the terms: -40 + 19t + 3t2 = 40 + -40 Combine like terms: 40 + -40 = 0 -40 + 19t + 3t2 = 0 Factor a trinomial. (-8 + -1t)(5 + -3t) = 0Subproblem 1
Set the factor '(-8 + -1t)' equal to zero and attempt to solve: Simplifying -8 + -1t = 0 Solving -8 + -1t = 0 Move all terms containing t to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1t = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1t = 0 + 8 -1t = 0 + 8 Combine like terms: 0 + 8 = 8 -1t = 8 Divide each side by '-1'. t = -8 Simplifying t = -8Subproblem 2
Set the factor '(5 + -3t)' equal to zero and attempt to solve: Simplifying 5 + -3t = 0 Solving 5 + -3t = 0 Move all terms containing t to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3t = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -3t = 0 + -5 -3t = 0 + -5 Combine like terms: 0 + -5 = -5 -3t = -5 Divide each side by '-3'. t = 1.666666667 Simplifying t = 1.666666667Solution
t = {-8, 1.666666667}
| 5-7x=34 | | (x+6)(x-2)(x+3)=264 | | 3*5m-3= | | 4k-2k=-20 | | g=7f+h | | x+5=2y-20 | | y=-3x^4-18x^3-24x^2 | | 3-3*6+2=23 | | 3m^2-11m-60=0 | | 5+4m=37 | | 21=x+14+x+11 | | 0.666(x+6)=-18 | | 2x+2.50=10.50 | | 17=x+15+x+22 | | .15+.4x=.7x-.03 | | X-0.3(X)=10500 | | x-0.3x=10500 | | 14x=2x+1+11 | | 16=x+9+x+17 | | 24-x+2x=53 | | x^4+4x^3-16x-16=0 | | 3y+4=50 | | 19=2x-14+2x-15 | | X-.3x=10500 | | 0.24=x-x^2 | | 18=12+x+x+6 | | -x^2-18=90 | | 18x^3+3x^2-x=0 | | n^2-5n-10=-11 | | 4y+5+3y= | | 2x+7-7=-39 | | ln(x+4)+7=32 |